Candida auris emergence in the Himalayan foothills: First case report from Uttarakhand, India - Suneeta Meena; Ranjana Rohilla; Neelam Kaistha; Arpana Singh; Pratima Gupta (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Candida auris is a rapidly emerging fungus, which is considered globally a cause of concern for public health. This report describes the first case of C. auris fungemia from a tertiary care hospital in the hilly state of Uttarakhand in India. Case report: The patient was a 37-year-old female who underwent a Whipple procedure for the carcinoma of the head of the pancreas. She developed fever 12 days after the operation while recovering from surgery in the hospital. Blood culture yielded C. auris which was identified by the matrix-assisted laser desorption/ionization-time of flight mass spectrometry (Bruker Daltonics, Germany). The patient was successfully treated with caspofungin. Conclusion: In conclusion, C. auris is potentially multidrug resistant, resulting in nosocomial outbreaks and sporadic infections which can be potentially prevented when identified early by implementing contact precautionsBackground and Purpose: Candida auris is a rapidly emerging fungus, which is considered globally a cause of concern for public health. This report describes the first case of C. auris fungemia from a tertiary care hospital in the hilly state of Uttarakhand in India. Case report: The patient was a 37-year-old female who underwent a Whipple procedure for the carcinoma of the head of the pancreas. She developed fever 12 days after the operation while recovering from surgery in the hospital. Blood culture yielded C. auris which was identified by the matrix-assisted laser desorption/ionization-time of flight mass spectrometry (Bruker Daltonics, Germany). The patient was successfully treated with caspofungin. Conclusion: In conclusion, C. auris is potentially multidrug resistant, resulting in nosocomial outbreaks and sporadic infections which can be potentially prevented when identified early by implementing contact precautions.